UMA NOVA ESPÃ‰CIE DE ARANHA DO GÃŠNERO ð˜Œð˜™ð˜ð˜–ð˜—ð˜ð˜–ð˜™ð˜ˆ (ð˜ˆð˜™ð˜Žð˜ð˜–ð˜—ð˜ð˜‹ð˜ˆð˜Œ-ð˜ˆð˜™ð˜ˆð˜•ð˜Œð˜ð˜•ð˜ˆð˜Œ) - Piza Junior, Salvador de Toledo (REVISTA DE AGRICULTURA, 2020)
UMA NOVA ESPÃ‰CIE DE ARANHA DO GÃŠNERO ð˜Œð˜™ð˜ð˜–ð˜—ð˜ð˜–ð˜™ð˜ˆ (ð˜ˆð˜™ð˜Žð˜ð˜–ð˜—ð˜ð˜‹ð˜ˆð˜Œ-ð˜ˆð˜™ð˜ˆð˜•ð˜Œð˜ð˜•ð˜ˆð˜Œ)